2021
DOI: 10.1063/5.0037765
|View full text |Cite
|
Sign up to set email alerts
|

Thermal conductivity of the n = 1–5 and 10 members of the (SrTiO3)nSrO Ruddlesden–Popper superlattices

Abstract: Unlike many superlattice structures, Ruddlesden–Popper phases have atomically abrupt interfaces useful for interrogating how periodic atomic layers affect thermal properties. Here, we measure the thermal conductivity in thin films of the n = 1–5 and 10 members of the (SrTiO3)nSrO Ruddlesden–Popper superlattices grown by molecular-beam epitaxy and compare the results to a single crystal of the n = 1 Ruddlesden–Popper SrLaAlO4. The thermal conductivity cross-plane to the superlattice layering (k33) is measured u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…The layered structure of the RP compounds would enhance the phonon scattering at the interfaces between the A 2 O 2 layer and perovskite layer and consequently reduce κ , which is of great importance for TE materials. Investigation on thermal conductivity in the thin films of the m = 1–5 and 10 members of the (SrTiO 3 ) m SrO RP superlattices showed that the m = 2 member had the lowest κ in this RP homologous series [ 9 ]. Significant reduction of κ values was observed in the layered (Sr 1− x RE x ) m +1 Ti m O 3 m +1 ( m = 1, 2) [ 10 ] and La 2−2 x Ca 1+2 x Mn 2 O 7 (0.75 ≤ x ≤ 1.0) [ 11 ] due to the intrinsic superlattice structure as compared to their perovskite phases.…”
Section: Introductionmentioning
confidence: 99%
“…The layered structure of the RP compounds would enhance the phonon scattering at the interfaces between the A 2 O 2 layer and perovskite layer and consequently reduce κ , which is of great importance for TE materials. Investigation on thermal conductivity in the thin films of the m = 1–5 and 10 members of the (SrTiO 3 ) m SrO RP superlattices showed that the m = 2 member had the lowest κ in this RP homologous series [ 9 ]. Significant reduction of κ values was observed in the layered (Sr 1− x RE x ) m +1 Ti m O 3 m +1 ( m = 1, 2) [ 10 ] and La 2−2 x Ca 1+2 x Mn 2 O 7 (0.75 ≤ x ≤ 1.0) [ 11 ] due to the intrinsic superlattice structure as compared to their perovskite phases.…”
Section: Introductionmentioning
confidence: 99%
“…Among others, RP phases based on STO or other perovskite oxides (SrRuO 3 , LaCuO 3 , NdNiO 3 etc.) exhibit very low dielectric losses (Dawley et al, 2020b;McCarthy et al, 1969;Lee et al, 2013b), strong magnetoresistance (Moritomo et al, 1996), improper ferroelectricity (Birol et al, 2011;Pitcher et al, 2015;Oh et al, 2015;Benedek et al, 2015) or low thermal conductivity, with attractive prospects for the design of highefficiency thermoelectric modules (Balachandran et al, 2017;Dawley et al, 2021;Wise et al, 2001;Kamba et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Instead, these authors reported a constant interfacial resistance ≈2 × 10 –9 K m 2 /W. A monotonic decrease was also observed in the thermal conductivity of (SrTiO 3 ) n SrO Ruddlesden–Popper superlattices, as the interface density increases …”
mentioning
confidence: 95%
“…A monotonic decrease was also observed in the thermal conductivity of (SrTiO 3 ) n SrO Ruddlesden–Popper superlattices, as the interface density increases. 23 …”
mentioning
confidence: 99%
See 1 more Smart Citation